2018
DOI: 10.1063/1.5030009
|View full text |Cite
|
Sign up to set email alerts
|

Symmetric autobalanced Ramsey interrogation for high-performance coherent-population-trapping vapor-cell atomic clock

Abstract: We report a high-performance pulsed coherent population trapping (CPT) Cs cell atomic clock using the implementation of a symmetric auto-balanced Ramsey (SABR) interrogation sequence. The latter method is found to reduce the light-power induced frequency shift by an order of magnitude compared to a previous experiment using a simple auto-balanced Ramsey interrogation. The contribution of this shift to the clock frequency stability is now rejected in the 10 −16 range at 10 4 s averaging time. Additional tricks,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(19 citation statements)
references
References 32 publications
(24 reference statements)
1
18
0
Order By: Relevance
“…The implementation of this approach can lead to significant improvement of the accuracy and long-term stability for a variety of types of atomic clocks. Also, it will be interesting to experimentally compare the one-loop CES/GCES method with the two-loop ABRS [37][38][39]. We believe that both methods have comparable efficiency for frequency stabilization, but CES/ GCES is technically simpler because only one feedback loop is required.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The implementation of this approach can lead to significant improvement of the accuracy and long-term stability for a variety of types of atomic clocks. Also, it will be interesting to experimentally compare the one-loop CES/GCES method with the two-loop ABRS [37][38][39]. We believe that both methods have comparable efficiency for frequency stabilization, but CES/ GCES is technically simpler because only one feedback loop is required.…”
Section: Resultsmentioning
confidence: 99%
“…Auto-balanced Ramsey spectroscopy (ABRS) is another effective approach that was first experimentally demonstrated in a 171 Yb + ion clock [37]. This intuitive approach was rigorously substantiated and generalized theoretically in [38], and also recently realized in a CPT atomic clock [39]. For ABRS, in addition to the stabilization of the clock frequency ω, a second loop controls a variable second (concomitant) parameter ξ, which is an adjustable property of the first and/or second Ramsey pulses.…”
mentioning
confidence: 99%
“…Thus, we have shown that the PM-ACS method always leads to zero shift of the stabilized frequency ω in an atomic clock,δ clock = 0. Note that in the general case the convergence of the joint iterative procedures (16) and (17) to the values (20) FIG. 5.…”
Section: A Pm-acs For Stepwise Modulation Of Powermentioning
confidence: 99%
“…This condition, when applied to both operating powers, P 1 and P 2 , is equivalent to Eqs. (19)- (20).…”
Section: A Pm-acs For Stepwise Modulation Of Powermentioning
confidence: 99%
See 1 more Smart Citation